Adult stem cells in bone and cartilage tissue engineering - Salgado, A. J. (2006)
The progressive increase in lif€ expectancy within the last century has led to the appearance of novel health related problems, some of those within the musculoskeletal Íield. Among the latter, one can find diseases such as osteoporosis, rheumatoid arthritis and bone cancer, just to mention some of the most relevant. Other related problems are those that arise from serious injuries, often leading to non-recoverable critical size defects. The therapies currently used to treat this type of diseases/injuries are based on the use of pharmaceutical agents, auto/allotransplant and synthetic materials. However, such solutions present a number of inconveniences and therefore, there is â constant search for novel therapeutic solutions. The appearance of a novel field of science called Tissue engileering brought some hope for the solution of the above mentioned problems. In this field, it is believed that by combining a 3D porous template - scaffold - with an adequate cell population, with osteo or chondrogenic potential, it will be possible to develop bone and cartilage tissue €quivalents that when implanted lr? vivo, could lead to the total regeneration of the affected area. This ideal cell population should have a series of properties, namely a high osteo and chondrogenic potential and at the same time, should be easily expandable and maintained in cuÌtures for long periods of time. Due to its natural and intrinsic properties, stem cells are on€ ofthe best available cell types. However, after this sen(ence, the readers may ask, "Whiçh Stem Cells?". During the last l0/15 yeaÍs, the scientific community witnessed and reported the appearanceo f several sourceso f stem cells with both osteo and chondrogenicp otential.T herefbre,t he present review intends to make an overview of data reported on different sources of adult stem cells (bone marfow, periosteum. adipose tissue, skeletal muscle and umbilical cord) for bone and cartilage regenerative medicine, namely those focusing on the differentiation potential of the latter as well as h y,vo proof of concept of their applicability. Simultaneously novel aspects of adult stem cells biotechnology such as their immunogenicc haraçteristicsa nd cell expansionm ethodologiesr vill also be put forward. The presentr eview also points out on issues such as the bone and caÍtiìage regenerativ€ market, and gives a brief description on bone and cartilage bone biology, so the readers can have a true idea of the cunent statc of the an, and how adult stem cells can be an added value to this field.